2018
DOI: 10.5194/cp-14-1881-2018
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-climatic variability in the southwestern Indian Ocean between 6000 and 3000 years ago

Abstract: Abstract. The “4.2 ka event” is frequently described as a major global climate anomaly between 4.2 and 3.9 ka, which defines the beginning of the current Meghalayan age in the Holocene epoch. The “event” has been disproportionately reported from proxy records from the Northern Hemisphere, but its climatic manifestation remains much less clear in the Southern Hemisphere. Here, we present highly resolved and chronologically well-constrained speleothem oxygen and carbon isotopes records between ∼6 and 3 ka from R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 67 publications
4
23
0
Order By: Relevance
“…In addition, the LAVI-4  18 O record also exhibits a high degree of replication with the PATA-1  18 O record from the nearby Patate cave between ~3000 and 6000 yr B.P. (37). Second, the theoretical range of calcite  18 O values [e.g., (54)…”
Section: Isotopic Equilibrium Testsmentioning
confidence: 72%
See 2 more Smart Citations
“…In addition, the LAVI-4  18 O record also exhibits a high degree of replication with the PATA-1  18 O record from the nearby Patate cave between ~3000 and 6000 yr B.P. (37). Second, the theoretical range of calcite  18 O values [e.g., (54)…”
Section: Isotopic Equilibrium Testsmentioning
confidence: 72%
“…The IsoGSM has been widely used for both modern and past climate simulations and has been shown to be in good agreement with the  18 O p observations from GNIP stations globally (38). The model-simulated  18 water vapor sources with substantially different isotopic compositions (37). Consequently, we have used these observations to interpret temporal variations in speleothem  18 O from Rodrigues in terms of hydroclimate variability over the SWIO.…”
Section: Regional Setting and Modern Climatementioning
confidence: 73%
See 1 more Smart Citation
“…Silva et al (2013) identified 21 species of cyanobacteria in stromatolites of the Lagoa Salgada, with the most representative being Microcoleus chthonoplastes and Lyngbya aestuarii, which are diazotrophic cyanobacteria present in coastal microbial mats. In hypersaline lakes, such as Lagoa Salgada, microbial mats precipitate CaCO 3 as a by-product of CO 2 capture through photosynthesis by cyanobacteria (Jonkers et al, 2003;Ludwig et al, 2005). The precipitation of CaCO 3 that generated the lithification of the microbial mats in the lake are caused by cyanobacteria that increase the pH through photosynthesis in a CaCO 3 supersaturated system (Decho and Kawaguchi, 2003).…”
Section: Sedimentary Processesmentioning
confidence: 99%
“…Between 9 and 4 Kyr BP, the climate signal from the WIN record is synchronous to the persistent northward position of the ITCZ (Figure 2c), which likely triggered or amplified the expansion of the WASM further northward during the AHP. Interestingly, synchronous growth hiatuses in two WIN2 and WIN3 records suggest a period of drought initiating around 4 Kyr BP (Figure 2a), coincident with the timing of several abrupt climate change events identified in many Holocene records around the world (e.g., Bond et al, 2001;Li et al, 2018;Marchant & Hooghiemstra, 2004;Mayewski et al, 2004;Roland et al, 2014). This abrupt climate event has indeed been linked to collapse of ancient civilizations in Northern Hemisphere subtropical regions, including Mesopotamia, Egypt, and the Indus Civilization [e.g., Staubwasser & Weiss, 2006;Weiss, 2016].…”
Section: Potential Mechanisms Behind the Northward Expansion Of The Wmentioning
confidence: 86%